Understanding the dechlorination of chlorinated hydrocarbons in the pyrolysis of mixed plastics - Jiang, Guozhan; Sanchez Monsalve, D. A.; Clough, Peter T.; Jiang, Ying; Leeke, Gary A. (American Chemical Society, 2021)
The dechlorination of chlorine containing hydrocarbons in pyrolysis vapor is poorly understood. In order to shed new light on the dechlorination mechanism, a model mixture composed of iso-octane doped with 2-chlorobutane, 2-chloroethylbenzene, and chlorobenzene was used to study the dechlorination of chlorinated hydrocarbons by alkali adsorption. These three chlorinated hydrocarbons were selected as they can be typically produced from the pyrolysis of mixed plastic waste containing polyvinyl chloride (PVC). The mixture is pumped continuously through a Na2CO3 or CaCO3/alumina bed, and GC-MS is used to identify the dechlorination products and to follow the dechlorination reactions. When chlorine is bonded to an aliphatic carbon with an adjacent aliphatic hydrogen, the chlorinated compound first undergoes a dehydrochlorination reaction to form HCl and olefins, and subsequently the HCl is reacted with the alkali in the absorbents. In our experiments, 2-chlorobutane is converted to 2-butene, and 2-chloroethylbenzene is converted to styrene. The formation of HCl and subsequent reaction with alkali components in the absorbent is verified by IR spectroscopy and XRD. In the presence of an alkali, the aliphatic chlorinated hydrocarbons underwent dechlorination at a temperature of 180 °C. The removal of chlorine from aromatic chlorinated compounds operates in a different mechanism, in which the C–Cl bond scission is promoted significantly by the presence of an alumina and hydrocarbon medium. It was found that chlorobenzene undergoes dechlorination forming phenol and benzene.
Keywords: Dechlorination; Chlorinated hydrocarbons; Pyrolysis; Mixed waste plastics; PVC